Effectiveness of Topical Treatment of Steroid and Calcineurin Inhibitor Combination Therapy for Atopic Dermatitis in Children at Skopje Hospital, Macedonia - Wilson, Maria Margareth (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease that often occurs in children. Topical treatments, including steroids and calcineurin inhibitors (CNI), are the main line of AD therapy. This study aimed to evaluate the effectiveness of topical treatment of combination steroid and CNI therapy for AD in children at Skopje Hospital, Macedonia. Methods: This research was a retrospective study involving 60 children with AD who were treated with combination therapy of steroids and CNIs for 8 weeks. Clinical data, including SCORAD (Severity of Atopic Dermatitis) score and extent of eczema, were collected before and after treatment. Results: Steroid and CNI combination therapy showed significant improvement in SCORAD score (p<0.001) and eczema extent (p<0.001) after 8 weeks of treatment. Reported side effects are minimal. Conclusion: Combination therapy of steroids and CNIs is an effective and safe treatment for AD in children.